Structure- and mechanism-guided design of single fluorescent protein-based biosensors - Nasu, Yusuke; Shen, Yi; Kramer, Luke; Campbell, Robert E. (Nature chemical biology, 2021)
Intensiometric genetically encoded biosensors, based on allosteric modulation of the fluorescence of a single fluorescent protein, are powerful tools for enabling imaging of neural activities and other cellular biochemical events. The archetypical example of such biosensors is the GCaMP series of Ca 2+ biosensors, which have been steadily improved over the past two decades and are now indispensable tools for neuroscience. However, no other biosensors have reached levels of performance, or had revolutionary impacts within specific disciplines, comparable to that of the Ca 2+ biosensors. Of the many reasons why this has been the case, a critical one has been a general black-box view of biosensor structure and mechanism. With this Perspective, we aim to summarize what is known about biosensor structure and mechanisms and, based on this foundation, provide guidelines to accelerate the development of a broader range of biosensors with performance comparable to that of the GCaMP series. Using extensive knowledge about the structures and mechanisms of genetically encoded fluorescent biosensors, this Perspective provides guidelines to aid and accelerate the development of an increasingly broad range of high-performance imaging tools.